STUDY OF THE PECULIARITIES OF THE EVOLUTION OF KARYOTYPE BASED ON THE ANALYSIS OF PHYLOGENETIC RELATIONS OF THE ACRIDIDAE FAMILY - Ольга Николаевна Гуляева; Людмила Васильевна Высоцкая (Медицина в Кузбассе)
Subject. Karyotype of 17-chromosome species of grasshoppers (the Acrididae family). Objective. Studying the ways of karyotype evolution on the basis of the analysis of phylogenetic relations of grasshoppers (the Acrididae family). Materials and methods. In the OLYMPUS BX 50 light microscope, the crushed differentially colored chromosome preparations of the twelve 17-chromosome species of the Acrididae family were analyzed. Results. The analysis of the value of centromeric index of the first chromosome revealed that the species Euthystira brachyptera, Podismopsis poppiusi from the Chrysochraontini tribe and the Euchorthippus pulvinatus species from the Gomphocerini tribe have a submetacentric first chromosome that does not reliably differ from the second chromosome. The analysis of the centromeric index of the second chromosome revealed the isolation of three species (Glyptobothrus biguttulus, Gomphocerus rufus and Stauroderus scalaris) from the other species of the Gomphocerini tribe. These species showed the increased value of the centromeric index of the second chromosome. The mutual increase in the centromeric index of the first and the second chromosomes in these species was detected. Conclusions. The phylogenetic affinity of the Euchorthippus pulvinatus species from the Gomphocerini tribe with the characteristic representatives of the Chrysochraontini tribe was revealed which indicates that during the karyotypic evolution of the representatives of these tribes, Robertson’s confluences included different chromosomes. The mutual increase in the centromeric index of the first and the second chromosomes in three species of the Gomphocerini tribe testifies that all the karyotype chromosomes evolve as a single whole. The size of chromosomes determines their ordered location in the interphase nucleus and is one of the main factors of natural selection. Extrapolation of data on the mechanisms of the evolution of grasshopper karyotypes to the human population makes it possible to use new medical genetic technologies for solving the priority problems to reduce the number of socially significant diseases which are based on the increasing aggressive impact of contemporary technogenic load on human.